Effect of partially hydrolyzed synbiotic formula milk on weight gain of late preterm and term infants—a multicenter study - Sahin, Suzan; Buyuktiryaki, Mehmet; Okur, Nilufer; Akcan, Abdullah Baris; Deveci, Mehmet Fatih; Yurttutan, Sadik; Gunes, Sezgin; Anik, Ayse; Ozdemir, Ramazan; Uygur, Ozgun; Oncel, Mehmet Yekta (Frontiers in Pediatrics, 2023)
Introduction Data on the effectiveness of hydrolyzed infant formula containing both pre- and probiotics (synbiotic formula) on the growth of infants is still scarce. This retrospective study was designed to evaluate the effect of a partially hydrolyzed synbiotic formula on growth parameters and the possible occurrence of major gastrointestinal adverse events or morbidities in infants born via cesarean section (C-section) delivery. Methods C-section-delivered term and late preterm infants who received either partially hydrolyzed synbiotic formula, standard formula, or maternal milk and followed at seven different hospitals from five different regions of Turkey, during a 1-year period with a minimum follow-up duration of 3 months were evaluated retrospectively. All the included infants were evaluated for their growth patterns and any kind of morbidity such as diarrhea, constipation, vomiting, infection, or history of hospitalization. Results A total of 198 infants (73 in the human milk group, 61 in the standard formula group, and 64 in the partially hydrolyzed synbiotic formula group) reached the final analysis. The groups were similar regarding their demographic and perinatal characteristics. No difference was observed between the three groups regarding gastrointestinal major side effects. Growth velocities of the infants in the human milk and partially hydrolyzed synbiotic formula groups during the first month of life were similar whereas the weight gain of infants in the standard formula group was significantly less than these two groups (p < 0.001). Growth velocities were similar among the three groups between 1st and 3rd months of age. Discussion A partially hydrolyzed synbiotic formula provided better weight gain in late-preterm and term infants who were delivered via C-section delivery compared to the standard formula during the first month of life. This weight gain was similar to the infants receiving exclusively human milk. This difference was not observed in length and head circumference gain. No difference was observed in any of the parameters during the 1st–3rd months of age. Specially formulated partially hydrolyzed synbiotic formulas may reverse at least some of the negative impacts of C-section delivery on the infant and help to provide better growth, especially during the early periods of life.